Os espaços e os modos de ler na Educação Infantil - Freitas, Isabela Adriana Santos de [UNESP]; Nóbrega, Mariana Leite da [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work had as a main goal: understand the spaces and modalities of reading about early Childhood Education. About the specific objectives: a) understand the conception of baby library as a space of reading in the childhood education; b) point the miscellaneous modalities of reading offered to the children from 0 to 3 years old; c) differentiate storytelling from reading aloud; d) distinguish reader from listener. To this, the search was made with a methodological path the bibliographic research, based on conceptions of authors in the education area and is configured in a qualitative character, based on theoretical studies, enjoying the repositories and the database of Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) from 3 (three) different public university institutions in São Paulo, which are: Universidade de São Paulo (São Paulo University), Universidade Estadual de Campinas (Campinas State University) e Universidade Estadual Paulista (São Paulo State University) “Júlio de Mesquita Filho”. Having those studies in our minds, we concluded that baby library is a rich space for Childhood Education, reading mediations need to be thought and planned and can be made through reading aloud or storytelling. The reader differs from the listener, but both are moving towards understanding the text and new discoveries.

O presente trabalho teve por objetivo geral: compreender os espaços e as modalidades de leitura voltadas para a Educação Infantil. Como objetivos específicos: a) conhecer as concepções de bebeteca como espaço de leitura na Educação Infantil; b) levantar as diversas modalidades de leitura ofertadas para as crianças de 0 a 3 anos de idade; c) diferenciar contação de histórias de leitura em voz alta; d) distinguir leitor de ouvinte. Para tanto, a pesquisa seguiu como caminho metodológico a pesquisa bibliográfica, tendo como base as concepções de autores da área da Educação e se configura em um caráter qualitativo, baseada em estudos teóricos, desfrutando dos repositórios e do banco de dados da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) de 3 (três) instituições universitárias paulistas públicas, que são: Universidade de São Paulo (USP), Universidade Estadual de Campinas (UNICAMP) e Universidade Estadual Paulista “Júlio de Mesquita Filho” (UNESP). A partir dos estudos, concluímos que a bebeteca trata-se de um espaço rico para a Educação Infantil, as mediações de leitura precisam ser pensadas e planejadas e podem ser feitas por meio da leitura em voz alta ou contação de histórias. O leitor se diferencia do ouvinte, mas ambos caminham para a compreensão do texto e de novas descobertas.
The spaces and ways to read in Childhood Education
Keywords: Baby library; Childhood education; Reading spaces; Reading modes; Bebeteca; Educação infantil; Espaços de leitura; Modos de ler